Data from the fungal phyllosphere of Mediterranean plant species - Pajares-Murgó, Mariona; Garrido, Jose L.; Perea, Antonio J.; López-García, Alvaro; Alcántara, Julio M. (Dryad, 2022)
The phyllosphere is a wide and complex ecosystem that provides key support
for microbial diversity. Fungal communities inhabiting the leaf are
functionally variable and play important roles on plant performance.
Factors conditioning the arrival and colonization of fungal communities
will determine the phyllosphere fungal composition. Plant identity, leaf
functional traits and host plant phylogeny have been shown to be
regulators of the microbial colonization of the leaves and can be
considered as biotic filters determining the assembly of phyllosphere
fungal communities. By high-throughput sequencing, we analysed the
phyllosphere fungal communities from 38 Mediterranean woody plant species
in two forests of the south-eastern Iberian Peninsula. We analysed the
effect of plant species and site on fungal community composition. We also
tested the effect of leaf functional traits and plant phylogeny on plant
species differences in their fungal communities, and on the structure of
the plant-fungus interaction network. Plant species account for a larger
proportion than site in the variability of the composition of phyllosphere
fungal communities. Leaf traits and host phylogeny influence the arrival
and colonization of phyllosphere fungal communities across plant species.
Plants with pubescent leaves and phylogenetically closer harbour more
similar communities of decomposers, pathogens and epiphytes. Leaf habit
(i.e., evergreen vs. deciduous) also influences the community composition
of decomposer and epiphytic fungi. Leaf carbon, leaf water content and
leaf mass per area affect differentially each functional guild.
Plant-fungus interaction networks present a modular structure in which
plants belonging to the same module share more fungal species and are
phylogenetically closer. We provide evidence that even though phyllosphere
fungal communities are complex ecosystems, fungi with contrasting
relationships with the plant (decomposers, epiphytes and pathogens)
respond similarly to a common subset of leaf traits that impose physical
limitations to the assembly of phyllosphere fungal communities.
We selected 27 plant species from the Mediterranean mixed forests. A total
of 276 leaf samples from 138 individual plants were dried with sterilized
silica gel and kept at 4ºC until processing. Molecular characterization of
fungal communities is fully explained in Suppl. Material S2. Briefly,
extracted DNA were subjected to Illumina NovaSeq sequencing using the
fungal-specific primers ITS3 and ITS4. The library preparation and the
Illumina NovaSeq run were carried out by AllGenetics and Biology SL
(www.allgenetics.eu). The bioinformatic analysis included
removing sequencing primers and quality filtering of raw sequencing,
estimating error rates and inferring of Amplicon Sequence Variants (ASVs).
Taxonomic assignment was determined for each ASV against the UNITE
database v. 8.2., complemented with representative sequences of the plant
genera involved in the study. ASVs were clustered (97%) into Operational
Taxonomic Units (OTUs) that resemble species level. Finally, 1,462 OTUs
and 7,173,784 reads were obtained. Fungal functional guilds were
determined by matching OTUs’ assigned genera and the genus-guild database
FungalTraits.
Microsoft Excel Text Editor
Keywords: FOS: Biological sciences; Mediterranean forests; phyllosphere fungi; Community assembly; leaf functional traits; plant-fungus interaction network; plant pathogenic fungi; plant epiphytic fungi